Early career training and development of academic independence: a case of life sciences in Japan. Issue 12 (2nd December 2021) - Yoshioka-Kobayashi, Tohru; Shibayama, Sotaro
ABSTRACT: Academic training is the initial step for junior scientists to learn to develop into independent scientists. This study investigates how supervisors decide to employ different approaches of early-career research training, and how these approaches influence the degree of trainees' independence in their later careers. Drawing on survey and bibliometric data of life scientists in Japanese universities, this study presents the following findings. First, if scientists are allowed higher autonomy in upstream research functions in early-career training, they later tend to attain greater organizational independence with higher organizational ranks. Second, if scientists are encouraged to deviate from conventional research topics during early-career training, they later tend to achieve greater cognitive independence by producing original research output. Third, the differences in the training approaches chosen by individual supervisors are influenced by the training that they had received in their early-career training. Overall, the study suggests that training approaches and independence of scientists are socialized in the local training context and passed down from one generation to the next.